Numerical simulation of mold filling and particulate flow of A356/SiCp indirect squeeze casting. (May 2020) - Hu, Qiyao; Zhao, Haidong; Long, Han; Dong, Puyun; Zhu, Gang
In this investigation, a mathematical model based on the dispersed phase model and multiphase flow principle was introduced, and applied to simulate the mold filling and particulate flow of particulate reinforced metal matrix composites casting. Experiments of spiral-square shaped indirect squeeze castings of A356/50 µm SiCp were conducted to validate the established model. The SiCp fractions in the casting different locations were quantitatively measured with micro digital image analysis system and were compared with the simulation results. It was found that particulate fractions and distribution patterns at different locations were quite different along the filling distance. The experimental and simulated results about the SiCp distribution in the castings show acceptable agreement. Further, the effect of fluid flow and particulate trajectories on the particulate distribution was analyzed and discussed. The research has shown the validity of application of the model for practical particulate reinforced Al-based composites casting.